Design of a miRNA sponge for the miR-17 miRNA family as a therapeutic strategy against vulvar carcinoma. Issue 6 (December 2015) - de Melo Maia, Beatriz; Ling, Hui; Monroig, Paloma; Ciccone, Maria; Soares, Fernando A.; Calin, George A.; Rocha, Rafael M.
Abstract: Dysregulation of microRNAs has been studied thoroughly, and has been observed in a variety of tumors including vulvar carcinomas, a rare type of gynecological tumor with increasing incidence. However, very few therapeutic alternatives have reached the clinical setting, and there is an urgent unmet need to develop novel strategies for patients with this tumor type. Thus, a microRNA (miRNA) sponge for the miR-17 miRNA family was designed, synthesized and validated in vitro in order to explore a new therapeutic strategy based on inhibiting this oncogenic miRNA family in vulvar cancer. Members of the miR-17 family were evaluated for expression in a vulvar tumor cell line (SW954) and 20 HPV negative formalin-fixed paraffin-embedded (FFPE) samples by quantitative real-time PCR (qRT-PCR). Six in tandem, bulged sequences that were complementary to these miRNAs were designed, synthesized, cloned, and transfected into SW954 cells. A luciferase reporter assay with a psiCheck2 vector was used to test the specificity of the sponge sequences for miR-17 family miRNA binding. Taqman qRT-PCR was used to test how the sponges affected miRNA expression. In FFPE samples, higher expression of miR-20a and miR-106a correlated with deeper tumor invasion (P = 0.0187 and P = 0.0404, respectively). The luciferase reporter assay validated the specificity of the sponge for miR-17 family members. Using qRT-PCR, we confirmed this specificity with decreased expression in 5 (out of six) miRNAs of the miR-17 family in SW954 cells. Although our results are preliminary, these results demonstrate that these miRNA sponges are potent inhibitors of the miR-17 family of miRNAs in SW954. Therefore, this miRNA-specific sponge may be developed into a novel therapeutic treatment for patients with vulvar cancer. Highlights: Some of the miR-17 family members present clinical importance in vulvar cancer. Sponge constructs were shown to be effective in downregulating miR-17 family members in vulvar cancer, in vitro . miRNA-specific sponges may be a therapeutic tool for patients with vulvar cancer.